Minoranze e diritto: spinte nazional sovraniste e semi di neoconfessionalismo in Lituania : al vaglio della Corte di Strasburgo le relazioni pericolose tra Chiesa e Stato - Pettinato, Cristiana Maria (Il diritto ecclesiastico, 2022)
Minorities and law. Sovereign national thrust and seeds of neoconfessionalism in Lithuania. On the screen of Strasbourg Court the dangerous relations between Church and State · The examination of this ruling of the echr shows how in some parts of Europe seeds of neo-confessionalism are still germinating due to the historical relations between so-called majority churches and the political events of the States. The clear position of the echr is that these are situations to be corrected in the name of the shared principles of secularism and non-discrimination and the protection of religious freedom.